NAZHIR RELIGIOSITY AS AN OPERATIONAL GOVERNANCE MECHANISM: RETHINKING ACCOUNTABILITY IN PRODUCTIVE WAQF INSTITUTIONS - Hendi Suhendi; M. Fauzi Arif (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
Productive waqf has gained increasing recognition as a strategic instrument within the Islamic social finance ecosystem, creating growing demands for governance systems that are both professionally managed and ethically grounded. While previous studies have largely examined waqf governance through structural, regulatory, and performance-oriented perspectives, limited attention has been given to how nazhir religiosity shapes governance practices in everyday organizational settings. This study addresses this gap by investigating how nazhir religiosity functions as an operational governance mechanism influencing accountability and governance practices in productive waqf institutions. Using an interpretive qualitative approach and a case study strategy, the research was conducted at Sinergi Foundation, an Indonesian Islamic philanthropic institution actively managing productive waqf programs. Data were collected through in-depth interviews with waqf managers, donors, and beneficiaries, complemented by institutional document analysis, and analyzed using thematic analysis. The findings reveal that nazhir religiosity operates through four interconnected governance mechanisms: ethical decision filtering, stewardship-oriented governance, multidimensional accountability construction, and the negotiation between religious values and institutional demands. Religiosity functions not merely as a personal belief system but as a source of managerial rationality that shapes strategic decision-making, risk assessment, resource allocation, and accountability practices. Accountability is understood as a multidimensional responsibility encompassing financial, social, ethical, and spiritual obligations toward donors, beneficiaries, society, and God. The study further finds that the influence of religiosity is mediated by organizational capacity, professional management requirements, and regulatory pressures, creating ongoing tensions between managerial efficiency and broader social objectives. This study contributes to waqf governance literature by reconceptualizing religiosity as an embedded governance mechanism and extends values-based leadership and Islamic accountability scholarship within faith-based organizations. The findings also provide practical insights for strengthening governance, accountability, and sustainability in productive waqf institutions.